1990
DOI: 10.1093/fampra/7.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centredness in the Consultation. 2: Does it Really Make a Difference?

Abstract: The major purpose of this study was to test the hypothesis that patient-centredness in the consultation was associated with improved patient outcomes. Patient-centred care was defined as care in which the doctor responded to the patient in such a way as to allow the patient to express all of his or her reasons for coming, including: symptoms, thoughts, feelings and expectations. The study took place in the offices of six family doctors. All consultations were audiotaped and the patients completed a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(111 citation statements)
references
References 0 publications
2
98
0
11
Order By: Relevance
“…A patient-centered approach is increasingly being considered a paradigm for high-quality interpersonal care. There is still a lack of consistent research evidence linking patient-centered care to improved patient outcomes, 8,[13][14][15][16][17] but it has been demonstrated that a practice style emphasizing patient activation is associated with significantly lower primary care charges. 18 Moreover, there is emerging evidence for an association between patient-centered communication and the utilization of medical resources.…”
mentioning
confidence: 99%
“…A patient-centered approach is increasingly being considered a paradigm for high-quality interpersonal care. There is still a lack of consistent research evidence linking patient-centered care to improved patient outcomes, 8,[13][14][15][16][17] but it has been demonstrated that a practice style emphasizing patient activation is associated with significantly lower primary care charges. 18 Moreover, there is emerging evidence for an association between patient-centered communication and the utilization of medical resources.…”
mentioning
confidence: 99%
“…PCC refers to communication that has 3 goals for health care providers: (1) seeking to understand patients' perspectives of their problems such that patients' reasons for visit, feelings, ideas, functioning, and expectations are on equal footing with the diagnostic imperative 9 -12 ; (2) understanding patients' psychosocial context, which means that health care providers need to explore patients' family, work, and social situation; and (3) encouraging participatory decision making in which health care providers seek to explain the diagnosis and treatment plans in understandable language and encourage patients to ask questions and engage in dialogue about the diagnosis and treatment plan. PCC is associated with higher levels of satisfaction, [13][14][15][16] and improved biomedical and functional outcomes, [17][18][19][20] and may also be associated with higher rates of detection of mental and emotional distress. [21][22][23][24][25][26][27][28][29][30] The aim of this study was to examine the influence of accompanied visits on physician-patient communication.…”
mentioning
confidence: 99%
“…In South Africa, Henbest et al showed a large and significant difference in the percent of satisfied patients, 15 percent in the not so patient-centered visits versus 46 percent satisfied after the highly patient-centered visits. [13] In Spain, Moral et al's trial demonstrated significantly higher patient perceptions in the intervention group (whose family doctor had received patient-centered training), 55 percent versus 29 percent. [14] With regard to patient health outcomes, results are mixed in the general patient-provider communication literature but with regard to family medicine and patient-centered care, results are promising.…”
Section: Studies Conducted Around the Worldmentioning
confidence: 99%
“…'n›n yapt›¤› çal›flmada hasta merkezli olmayan ve hasta merkezli olan görüflmeler aras›n-da hasta doyumu aç›s›ndan %15'e %46 gibi büyük ve anlaml› bir fark saptanm›flt›r. [13] ‹spanya'da Moral ve ark., aile hekimleri hasta merkezli bir e¤itim alm›fl olan müda-hale grubu ile kontrol grubu aras›nda, hasta alg›lar›nda %55'e %29'luk bir fark göstermifllerdir. [14] Hasta ç›kt›lar› göz önüne al›nd›¤›nda ise sonuçlar, genel hasta hekim iletiflimi aç›s›ndan karmafl›k olmakla birlikte, aile hekimli¤i ve hasta merkezli bak›m aç›s›ndan umut vericidir.…”
Section: Bireyin Bir Bütün Olarak Kavranmas›unclassified